ACTIVE LEARNING APPLICATION IN ISLAMIC RELIGIOUS EDUCATION - Rahman, Yudi Ardian (Tsaqofah : Jurnal Pendidikan Islam, 2021)
Learning is a process of knowledge transfer conducted by educators to students within the scope of a particular place and time. The learning can be done by using several kinds of learning models. One of them is the active learning model. Active learning-based PAI learning is a model of PAI learning that prioritizes the activeness of students in the learning process. This is intended to maximize the learning process, namely to obtain high student achievement. Therefore, when using active learning, it is intended to be used to improve the quality of Islamic religious education learning outcomes. The inverse statement is that there are not a few Islamic Education teachers who teach their students with learning that can be said to be relatively boring, monotonous, inflexible, so they find it difficult to be able to accept what is conveyed by the teacher. Active learning in PAI learning seeks to make learning not only the teacher as the center of learning, but designing a lesson so that students are active, participating in carrying out learning activities. For example, a student actively asks questions, thinks, does practices related to learning materials. The quality of material delivery from a teacher determines the success of learning. Therefore, educators are expected to be able to convey the content of learning materials to the maximum as worthy of optimal performance which includes methods, strategies, approaches and others. When the teacher does not pay attention to student activeness in the delivery of material, then the learning is not yet effective. A learning can be classified as effective, that is, if educators and students can play a joint role in carrying out learning and teaching activities. This means that an active reciprocal interaction relationship can occur in the process, namely the teacher as a communicator, is able to convey and provide sessions or time for students to ask questions, argue, and so on, while students as communicants, can follow the teacher's delivery and are able to place themselves to communicate with the teacher as a member of communication effectively. Keywords: Active learning, effective learning, and active participation.